Tradition and Modernity : Christian and Muslim Perspectives - Marshall, David (Book collections on Project MUSE., 2013)
Tradition and Modernity focuses on how Christians and Muslims connect their traditions to modernity, looking especially at understandings of history, changing patterns of authority, and approaches to freedom. The volume includes a selection of relevant texts from 19th- and 20th-century thinkers, from John Henry Newman to Tariq Ramadan, accompanied by illuminating commentaries.